Pelatihan kewirausahaan inovasi pemasaran dan varian rasa era digital Desa Kedungmaron Kabupaten Madiun - Iskandar, Dicky; Widiasmara, Anny (Penamas: Journal of Community Service, 2022)
Small and Medium Enterprises (SMEs) of tempeh chips in Madiun Regency are experiencing rapid development, including the "NAJA" tempeh chips produced by Mrs. Yuli. So far, the problems faced are only word-of-mouth promotion and have not done online marketing, and there are no product variants. The 2021 Innovation Talent Team conducts marketing innovation training based on Digital marketing in collaboration with Shopee Indonesia and provides flavor variants for tempeh chips. The method used is field observation, data collection, and training on Marketing Innovation, Flavor Variants, and Packaging. The results of consumer training are easier to view and order products via Instagram, Whatsapp and telephone by cooperating with Shopee E-commerce and making permits. This training also provides ways to make packaging neater and more efficient. Flavor variants include original taste, balado, roast beef, grilled corn, chicken onions, spicy. Tempe chips UKM "NAJA" can expand its business reach so that many people can recognize tempeh chips with various flavors, and the market share is getting wider.